2016
DOI: 10.1021/acs.jmedchem.6b00306
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Brigatinib (AP26113), a Phosphine Oxide-Containing, Potent, Orally Active Inhibitor of Anaplastic Lymphoma Kinase

Abstract: In the treatment of echinoderm microtubule-associated protein-like 4 (EML4)-anaplastic lymphoma kinase positive (ALK+) non-small-cell lung cancer (NSCLC), secondary mutations within the ALK kinase domain have emerged as a major resistance mechanism to both first- and second-generation ALK inhibitors. This report describes the design and synthesis of a series of 2,4-diarylaminopyrimidine-based potent and selective ALK inhibitors culminating in identification of the investigational clinical candidate brigatinib.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
244
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(253 citation statements)
references
References 56 publications
0
244
0
Order By: Relevance
“…20 In preclinical models, brigatinib potently inhibited all ALK resistance mutations tested, including G1202R, and overcame mechanisms of resistance to other ALK inhibitors at clinically achievable brigatinib levels. 21 In an ongoing phase I/II clinical trial (NCT01449461), brigatinib yielded promising antitumor activity (confirmed ORR, 62%; median PFS, 12.9 months) in patients with advanced ALK-positive NSCLC previously treated with crizotinib.…”
Section: Introductionmentioning
confidence: 99%
“…20 In preclinical models, brigatinib potently inhibited all ALK resistance mutations tested, including G1202R, and overcame mechanisms of resistance to other ALK inhibitors at clinically achievable brigatinib levels. 21 In an ongoing phase I/II clinical trial (NCT01449461), brigatinib yielded promising antitumor activity (confirmed ORR, 62%; median PFS, 12.9 months) in patients with advanced ALK-positive NSCLC previously treated with crizotinib.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, major unique mutational liabilities of ceritinib (L1152R/P and L1198F) and alectinib (I1171N and V1180L), are shown to result from their differing molecular structures and interactions with ALK compared with brigatinib. Notably, the dimethylphosphine oxide moiety present on the C4 aniline of brigatinib is critical for balancing ALK potency and selectivity over the highly homologous IGF-1R and INSR kinases (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, brigatinib (AP26113) is a potent ALK inhibitor that inhibits most crizotinib-resistant ALK mutants (124129). In the phase II ALTA trial, 222 patients with advanced ALK -positive NSCLC who progressed on crizotinib were randomized to two different dosing schedules of brigatinib.…”
Section: Developing Strategies To Overcome Resistancementioning
confidence: 99%